Pulmonary tuberculosis and drug resistance in Dhaka central jail, the largest prison in Bangladesh. - Sayera Banu; Arman Hossain; Mohammad Khaja Mafij Uddin; Muhammad Reaj Uddin; Tahmeed Ahmed; Razia Khatun; Asif Mujtaba Mahmud; Khurshid Alam Hyder; Afzalunnessa Binte Lutfor; Md Sirajul Karim; Khalequ Zaman; Md Ashraful Islam Khan; et al. (PLoS ONE, 2010)
BACKGROUND: There are limited data on TB among prison inmates in Bangladesh. The aim of the study was to determine the prevalence of pulmonary tuberculosis (TB), its drug resistance and risk factors in Dhaka Central Jail, the largest prison in Bangladesh. METHODS: Cross sectional survey with, active screening of a total number of 11,001 inmates over a period of 2 years. Sputum samples from TB suspects were taken for acid- fast bacilli (AFB) microscopy, culture and drug susceptibility testing. RESULTS: Among 1,781 TB suspects 245 (13.8%) were positive for AFB on microscopy and/or culture. The prevalence rate of sputum- positive pulmonary TB was 2,227/100,000. Fifty three cases (21.6% of 245 cases) were AFB- negative on microscopy but were found positive on culture. Resistance to isoniazid, rifampicin, streptomycin and ethambutol was 11.4%, 0.8%, 22.4% and 6.5% respectively. No multidrug resistance was observed. The main risk factors of TB in prison were exposure to TB patients (adjusted odds ratio 3.16, 95% CI 2.36-4.21), previous imprisonment (1.86, 1.38-2.50), longer duration of stay in prison (17.5 months for TB cases; 1.004, 1.001-1.006) and low body mass index which is less than 18.5 kg/m(2) (5.37, 4.02-7.16). CONCLUSIONS: The study results revealed a very high prevalence of TB in the prison population in Dhaka Central Jail. Entry examinations and active symptom screening among inmates are important to control TB transmission inside the prison. Identifying undiagnosed smear-negative TB cases remains a challenge to combat this deadly disease in this difficult setting.